Beijing sublineages of Mycobacterium tuberculosis differ in pathogenicity in the guinea pig - Kato-Maeda, Midori; Shanley, Crystal A; Ackart, David; Jarlsberg, Leah G; Shang, Shaobin; Obregon-Henao, Andres; Harton, Marisabel; Basaraba, Randall J; Henao-Tamayo, Marcela; Barrozo, Joyce C; Rose, Jordan; Kawamura, L Masae; et al. (Clinical and vaccine immunology, 2012)
The Beijing family of Mycobacterium tuberculosis strains is part of lineage 2 (also known as the East Asian lineage). In clinical studies, we have observed that isolates from the sublineage RD207 of lineage 2 were more readily transmitted among humans. To investigate the basis for this difference, we tested representative strains with the characteristic Beijing spoligotype from four of the five sublineages of lineage 2 in the guinea pig model and subjected these strains to comparative whole-genome sequencing. The results of these studies showed that all of the clinical strains were capable of growing and causing lung pathology in guinea pigs after low-dose aerosol exposure. Differences between the abilities of the four sublineages to grow in the lungs of these animals were not overt, but members of RD207 were significantly more pathogenic, resulting in severe lung damage. The RD207 strains also induced much higher levels of markers associated with regulatory T cells and showed a significant loss of activated T cells in the lungs over the course of the infections. Whole-genome sequencing of the strains revealed mutations specific for RD207 which may explain this difference. Based on these data, we hypothesize that the sublineages of M. tuberculosis are associated with distinct pathological and clinical phenotypes and that these differences influence the transmissibility of particular M. tuberculosis strains in human populations.